ACCURACY ANALYSIS OF GALILEO CODE POSITIONING FOR UAV - Klaudia CYBULSKA-GAC; Kamil KRASUSKI; Adam CIEĆKO (Scientific Journal of Silesian University of Technology. Series Transport)
Official ICAO certification for the Galileo satellite navigation system is currently being implemented for aeronautical applications. Hence, experimental studies are needed to verify the performance of Galileo for kinematic positioning of the user in aviation. The main objective of this work is to present an optimal computational strategy for determining the user's position and the accuracy parameter of Galileo positioning in civil aviation. The paper uses the least squares method and Kalman filtering to calculate the user position. The calculations were performed in two independent Galileo observation processing software, i.e., RTKLIB and Emlid Studio. Galileo navigation and observation data acquired from a DJI Matrice RTK300 unmanned platform was used in the calculations. The Galileo SPP code method algorithm was used to determine the UAV coordinates. The RTKLIB application uses a solution based on the least squares method model to determine user coordinates using the SPP method. The Emlid Studio application, respectively, is based on the Kalman filtering algorithm. On this basis, the UAV positions were determined for the two computational strategies, and the Galileo positioning accuracy was then determined in the form of position errors and RMS errors. The study shows that Emlid Studio software improves Galileo's kinematic positioning accuracy by between 15 and 65% over the results obtained from the RTKLIB solution. The flight tests carried out, the software used, and the computational strategies can be utilized for other global GNSS systems.